Through a Glass Darkly : essays in the religious imagination - Hawley, John C.; Cary, Norman R.; Chang, Sheng-Tai; Costa, Gavin D'; Crowley, Paul G.; Franke, William; Greeley, Andrew; Hawley, John C.; Kristof, Jane; Lievestro, Christiaan Theodoor; Mormando, Franco; Oakes, Edward T.; et al. (New York : Fordham University Press, 1996)
These essays, interdisciplinary in their approach, demonstrate the variegation of the religious imagination from the broadest historical and denominational scope. By examining the works of philosophers and theologians, of poets, painters and novelists - from Saint Mark to Jacques Derrida and from Erasmus, Loyola and Milton to Rouault and to Andrew Greeley - the essayists seek to answer the question Jesus posed to His disciples : Who do you say that I am? and to anticipate the equally contentious query How do you say who I am? The essays together explore the religious imagination through the question of transcendence, using both the age-old Christian imagination and the contemporary world wherein the divisiions between religious cultures are less fixed, an age of imaginative permeability where the absence of God is as present as the presence of God.
Engels
boek